Simultaneously Improved Thermoelectric and Mechanical Properties Driven by MgB2 Doping in Bi0.4Sb1.6Te3 Based Alloys. (14th May 2021) - Qin, Haixu; Cui, Bo; Wang, Wei; Sun, Sibo; Qin, Dandan; Guo, Muchun; Xie, Liangjun; Guo, Fengkai; Cai, Wei; Sui, Jiehe
Abstract: Bi2 Te3 ‐based alloys are the most mature and widely used thermoelectric materials since their z T value has been significantly improved in past decades. However, the poor mechanical strength and machinability derived from the easy cleavage along basal planes not only produce many scraps in the device fabrication process but also lead the devices unstable in the actual service. In this work, a tiny amount of MgB2 is induced in the Bi0.4 Sb1.6 Te3 alloy to simultaneously enhance the thermoelectric and mechanical properties. In detail, magnesium atoms occupy the bismuth/antimony sites to optimize the carrier concentration and suppress the bipolar effect, pushing the average z T value up to 1.16 ranging from 300 to 500 K, which catches up with the current highest level in p ‐type Bi2 Te3 ‐based materials. Moreover, the precipitation phase, boron nanoparticles, distributed at the grain boundaries can effectively improve the compressive strength from 166 to 239 MPa. The prominent thermoelectric and mechanical properties endow the materials with great potential for commercial applications. Abstract : MgB2 doping is used to simultaneously enhance the thermoelectric and mechanical properties Bi0.4 Sb1.6 Te3 alloy, which not only shifts the average zT value up to1.16 between 300 and 500 K but also obtains a record high compressive strength of 239 MPa, making our materials more attractive for the widespread application.